Government Policies in Combating COVID-19 Pandemic in Pakistan: A Gender-based Perspective (Journal of Fatima Jinnah Medical University, 2024)
Background: One of the most significant determinants of risk perceptions and coping mechanisms is gender, which reflects the public's propensity to embrace health initiatives and exercise caution. This study aims to understand the gender differences in perspective regarding government policies in combating COVID-19 pandemic.Subjects and methods: This analytical cross-sectional study was conducted as an online google survey from April to September 2021 in Lahore using a non-probability convenience sampling technique. SPSS version 23 was used for the analysis of the data, which was gathered using a self-structured questionnaire from 200 participants. Chi-square test was applied to deal with qualitative variables and a p-value
Keywords: Perceptions; policies; pandemic